(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The paper summarizes the results of long-term study of Caucasian persimmon in the southern region of Ukraine in terms of its economic use as an ornamental and fruit crops as well as rootstock for other types of persimmons and their hybrids. In the southern region of Ukraine Caucasian persimmon may find practical use as rootstock for eastern persimmon and its hybrids only in places where the absolute minimum temperature is not lower than – 18–20 ˚ C: the Southern coast of Crimea. In colder climates it is better to use persimmon Virginia as a rootstock. The usage of Caucasian persimmon as fruit crops in the southern region of Ukraine is unrealistically primarily because of its low hardiness. Persimmon Virginia is more likely for this purpose; it is more winter-hardy and fruitful.